(untitled) (Journal of Engineering, 2016)
This paper studies the combination fluid viscous dampers in the outrigger system to add supplementary damping into the structure, which purpose to remove the dependability of the structure to lower variable intrinsic damping. It works by connecting the central core, comprising either shear walls or braced frames, to the outer perimeter columns. The modal considered is a 36 storey square high rise reinforced concrete building. By constructing a discrete lumped mass model, and using frequency-based response function, two systems of dampers, parallel and series systems are studied. The maximum lateral load at the top of the building is calculated, and this load will be applied at every floor of the building, giving a conservative solution. For static study Equivalent Lateral Force (ELF) was conducted. MATLAB software, has been used in this study. From analysis data, it is observed that the parallel system of dampers result lower amplitude of vibration and achieved more efficiently compared to the series system, and the horizontal displacement for each configurations by using MATLAB software is less than the analytical solution using a uniformly distributed load of 36 nodal point forces that divided the total height.